Effect of Clinical and Subclinical Hypothyroidism on Fetal Outcomes among Pregnant Women: A Sub-Specialty Department Experience (Journal of National Institute of Neurosciences Bangladesh, 2021)
Background: Hypothyroidism can effect on the fetal outcomes during pregnancy.Objective: The purpose of the present study was to compare the effects of clical and subclinical hypothyroidism on fetal outcomes among pregnant women.Methodology: This cohort study was conducted in the Feto-Maternal Department of Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from a period of 6 months dated from September 2019 to February 2020. All cases of the clinical and sub-clinical hypothyroid pregnant women admitted in this department. Fetal outcomes of clinical and sub-clinical hypothyroid pregnant women during delivery were recorded. Findings of the cases recorded carefully.Result: A total number of 75 patients were recruited for this study who were divided in to two group designated as group I or sub clinical hypothyroidism and group II or clinical hypothyroidism. Fetal distress was 22(51.1%) cases in group I and 9(33.3%) cases in group II. The fetal outcome of the study patients had observed that 8(27.6%) and 12(80.0%) of the baby had low (